Restorative Justice in Indonesian Law on Juvenile Criminal Justice System and Its Implications for Social Work - Suharto, Edi (2021)
The study was motivated by Indonesian Law on Juvenile Criminal Justice System, which is now starting to take effect based on the restorative justice paradigm. The study aims to analyze the restorative justice in the juvenile system as the settlement of criminal cases together with related parties in order to find a fair settlement by emphasizing restoration to its original state. By using the socio-legal approach, the results recommend that to achieve this restorative justice, efforts are made to diversify or transfer the settlement of juvenile cases from the criminal justice process to the non-criminal court process. It is in this diversion effort that it has an impact on social work. If previously social workers had a small role towards children in conflict with the law (ABH), now their role is bigger. So that it takes an increase in quality and quantity. The results would imply that increasing both quality and quantity must be followed by efforts such as education and training. Practical implications also denote the quality of social welfare service institutions be strengthened because this institution will accommodate ABH when the diversion effort is agreed upon by the parties